2012
DOI: 10.1261/rna.031369.111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the human PMR1 mRNA endonuclease as an alternatively processed product of the gene for peroxidasin-like protein

Abstract: The PMR1 endonuclease was discovered in Xenopus liver and identified as a member of the large and diverse peroxidase gene family. The peroxidase genes arose from multiple duplication and rearrangement events, and their high degree of sequence similarity confounded attempts to identify human PMR1. The functioning of PMR1 in mRNA decay depends on the phosphorylation of a tyrosine in the C-terminal polysome targeting domain by c-Src. The sequences of regions that are required for c-Src binding and phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The 57 kDa hPMR1 protein is cytoplasmic, and it is the only form of PXDNL detectable in a number of cancer cell lines, including U2OS, K562, MCF-7 and MDA-MB-231. We previously showed that the motility of U2OS cells was increased following expression of Xenopus PMR1 from a tetracycline-inducible promoter ( 6 ), and similar results were seen for hPMR1 in MCF-7 breast cancer cells ( 5 ). MCF-7 cells are not particularly motile or invasive, but become both motile and invasive following suppression of miR-200 family microRNAs ( 7 ).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…The 57 kDa hPMR1 protein is cytoplasmic, and it is the only form of PXDNL detectable in a number of cancer cell lines, including U2OS, K562, MCF-7 and MDA-MB-231. We previously showed that the motility of U2OS cells was increased following expression of Xenopus PMR1 from a tetracycline-inducible promoter ( 6 ), and similar results were seen for hPMR1 in MCF-7 breast cancer cells ( 5 ). MCF-7 cells are not particularly motile or invasive, but become both motile and invasive following suppression of miR-200 family microRNAs ( 7 ).…”
Section: Introductionsupporting
confidence: 58%
“…The creation of tetracycline-inducible lines of MCF-7 cells and cells knocked down for hPMR1 were described in ( 5 ). These were maintained in RPMI-1640 supplemented with 10% fetal bovine serum (FBS), 2 mM l -glutamine, 1.0 mM sodium pyruvate, and 10 mM Hepes and 4.5 g/l glucose until 3 days before the start of each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we constructed a prognostic gene signature model by using multivariate Cox analysis, and screened 6 BC immunity-related feature genes (PXDNL, FABP7, STX11, PIGR, SHISAL2A, WDR17) which could be used as independent prognostic factors. PXDNL (Peroxidasin like), a member of the peroxidase gene family, has a variety of biological functions, including hormone biosynthesis, host defense and cell movement26 . A recent study by Li et al has reported that PXDNL is closely related to the development of BC, and the high expression of PXDNL is a potential independent prognostic indicator of BC27 .…”
mentioning
confidence: 99%